Assessment of lesser prairie-chicken translocation through survival, space use, and resource selection - Teige, Elisabeth Caroline (Kansas State University, 2021)
Translocation is defined as the deliberate movement of organisms from one site to another where the main objective is a conservation benefit. Translocations are used frequently as a management tool to restore or augment wildlife populations but generally have varying degrees of success. The lesser prairie-chicken (Tympanuchus pallidicinctus) is found in the southwestern Great Plains of the United States and currently occurs in four distinct ecoregions (Short-Grass Prairie/CRP Mosaic, Mixed-Grass Prairie, Sand Sagebrush Prairie, and Sand Shinnery Oak Prairie) across five states (Kansas, Colorado, Oklahoma, Texas, and New Mexico, USA). Recent estimates suggest the lesser prairie-chicken currently occupies only 15% of their estimated historical range. Within the current occupied range, lesser prairie-chicken populations have been experiencing moderate to severe population declines. Since a contemporary peak of an estimated 150,000 birds in the mid-1980s, lesser prairie-chicken populations have declined to an estimated abundance of 34,408 in 2020. The largest contemporary decline in population abundance and occupied range is occurring in the Sand Sagebrush Prairie Ecoregion. Historically, the Sand Sagebrush Prairie Ecoregion was the epicenter of the lesser prairie-chicken population despite a large area of vegetation in the ecoregion being decimated during the Dust Bowl of the 1930s. In 2020, only 171 birds were estimated for the ecoregion. In response to the extreme population decline and elevated extinction risk for the lesser prairie-chicken population in the Sand Sagebrush Prairie Ecoregion, myself, along with the Kansas Department of Wildlife and Parks, Colorado Parks and Wildlife, and U.S. Forest Service translocated lesser prairie-chickens from the Short-Grass Prairie/CRP Mosaic Ecoregion in northwest Kansas, where lesser prairie-chickens are currently most abundant, to release sites in sand sagebrush prairie landscapes on the U.S. Forest Service, Cimarron and Comanche National Grasslands in southwestern Kansas and southeastern Colorado, respectively. I captured, marked, translocated, and monitored 411 lesser prairie chickens during spring 2016-2019 to understand how translocation affects demographic rates, space use, and habitat selection for assessing translocation as a conservation tool for this declining prairie-grouse. My objectives were to estimate lek counts, nest success, reproductive success, adult survival, home range establishment and land cover composition, and selection of habitat vegetation characteristics at local and broad scales to assess lesser prairie-chickens response to translocation in a novel landscape. Within two weeks of release, 22.8% of birds either died or were never located. I used known-fate and nest survival models in Program MARK to determine adult survival and nest success of lesser prairie-chickens. I estimated breeding season survival for both males and females to be 0.44 ± 0.02 (SE) and nest success as 0.37 ± 0.04 (SE) but with a declining trend for the entire study period (2017-2020). Overall, vital rates were average to low and male high counts on established lek started to decline in 2021, two years following active translocation. Habitat availability in a novel environment may become an increasing concern as translocated lesser prairie-chickens have consistently larger home ranges than their native counterparts. Home ranges of translocated birds was comprised of greater area of Conservation Reserve Program land than any other cover type on the landscape. Lastly, on a local scale (300 m), I found little selection for vegetation at used locations, but lesser prairie-chickens used thicker and taller cover for nest sites. This vegetation use was expected and conveys the importance of the vegetation structure needed at a translocation release site. My results highlight the importance of land management conservation and its role in the conservation of lesser prairie-chicken populations. The translocation may have some short-term success but current vital rates of lesser prairie chickens may not be enough to overcome inherent limiting factors of the ecoregion for the population to become self-sustaining and the translocation to be deemed a long-term success.
Keywords: Lesser prairie-chicken; Translocation; Sand Sagebrush Prairie; Resource selection; Survival; Space use